2007
DOI: 10.1093/jxb/erm027
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of leakage in IRGA's leaf chambers of open gas exchange systems: quantification and its effects in photosynthesis parameterization

Abstract: The measurement of the response of net photosynthesis to leaf internal CO2 (i.e. A-Ci curves) is widely used for ecophysiological studies. Most studies did not consider CO2 exchange between the chamber and the surrounding air, especially at the two extremes of A-Ci curves, where large CO2 gradients are created, leading to erroneous estimations of A and Ci. A quantitative analysis of CO2 leakage in the chamber of a portable open gas exchange system (Li-6400, LI-COR Inc., NE, USA) was performed. In an empty cham… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
233
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 240 publications
(242 citation statements)
references
References 51 publications
8
233
0
1
Order By: Relevance
“…For the open gas exchange system, the diffusion leak of CO2 was readily detected as the apparent 'net photosynthesis' at various CO2 concentrations (Flexas et al, 2007). Unexpectedly, there was only a marginal effect on leakage caused by the isolation of the cup from the open Environ.…”
Section: Effects Of Leaksmentioning
confidence: 96%
See 2 more Smart Citations
“…For the open gas exchange system, the diffusion leak of CO2 was readily detected as the apparent 'net photosynthesis' at various CO2 concentrations (Flexas et al, 2007). Unexpectedly, there was only a marginal effect on leakage caused by the isolation of the cup from the open Environ.…”
Section: Effects Of Leaksmentioning
confidence: 96%
“…We estimated diffusion molar flow rate of CO2 (KCO2) and water vapor (KH2O) according to Flexas et al (2007) and Rodeghiero et al (2007). Previous studies (Lauer and Boyer, 1992;Boyer and Kawamitsu, 2011) have preferentially used paraffin/-lanolin (P/L) coat to prevent diffusion leaks in the gas exchange systems.…”
Section: Leak Testmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the respiration rate measured at low CO2 concentration was generally overestimated. A correction for leakage was necessary because it is hard to avoid CO2 exchange or leakage between the infrared gas analyzer (IRGA) chamber and the surrounding air (Pons & Welschen 2002, Shapiro et al 2004, Flexas et al 2007, Rodeghiero et al 2007). We corrected for CO2 leakage by diffusion in the Laisk method based on the following equation (eqn.…”
Section: Measurements and Data Processingmentioning
confidence: 99%
“…Some studies have proposed that the overestimation of RLL is caused by the CO2 acting as an inhibitor of certain enzymes (Brooks & Farquhar 1985, Kirschbaum & Farquhar 1987, Tjoelker et al 2001. However, a large number of studies suggest that leaf respiration changes with CO2 possibly due to small leaks or diffusion in the gas exchange measurement systems (Amthor et al 2001, Pons & Welschen 2002, Shapiro et al 2004, Flexas et al 2007, Rodeghiero et al 2007. Therefore, in this study RLL was corrected based on the method suggested by Li-Cor Inc (2004) to compensate the CO2 leakage in the Laisk method.…”
Section: Uncertainties In Day Respiration Estimatementioning
confidence: 99%